Determinants of Food Selections among International Travelers Towards Malaysian Cuisine - Hawaliana Selamat; Nor Farawahidah Mohd Khamis; Siti Nurhanifah Sulong; Siti Noraisah Dollah Abdullah; Siti Nor Fadillah Mohd Shariff (Information Management and Business Review, 2025)
Food plays a crucial role in the travel experience, serving as an important aspect of destination marketing to attract international travelers to Malaysia. Therefore, this study discovers the determinants of Malaysian food selections among travelers. A quantitative research approach was used in this study due to its effectiveness in data collection. A descriptive study was used to determine the motivational and psychological factors affecting the selection of Malaysian cuisine by international travelers. A non-probability, convenience sampling method was developed, consenting to the selection of any international travelers meeting the criteria. The target population for this study consisted of international travelers located in Kuala Lumpur. The selection of the population was travelers staying in Malaysia for a duration of three days to two weeks and who had tried Malaysian cuisine during their visit. Data was gathered through self-administered surveys of 398 travelers visiting Malaysia. The findings reveal a positive relationship between these motivational factors and travelers' intention to consume local food. The study suggests that experiencing local cuisine helps create positive, lasting memories, intensifying tourists' relationships with local attractions and enhancing their behavioral intentions.